Single-Session of Combined tDCS-TMS May Increase Therapeutic Effects in Subjects With Tinnitus - Bae, Eun Bit; Lee, Jun Ho; Song, Jae-Jin (Frontiers in Neurology, 2020)
To treat motor and psychiatric disorders, transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS) are world-widely in use in clinics. We combined these two types of neuromodulation technique to increase the effective response of a single session of neuromodulation in subjective tinnitus. Experimental groups with 80 tinnitus subjects consisted of four different treatment groups which are tDCS, tDCS with sham TMS, tDCS-TMS and TMS group. Subjects were given 1.5mA tDCS on the bi-frontal area and TMS stimulated contralateral single side of temporo-parietal cortex with 200 pulses at 1Hz stimulation. Comparing pre-treatment questionnaire scores to post-treatment questionnaire scores, all 4 groups showed statistically significant improvements. Although there was no significant difference among group comparison, the largest mean difference was shown in the combined group, especially for tinnitus intensity and tinnitus-related distress. Responders in the combined group were the highest for VAS intensity, maximum 80% of twenty subjects. To summarize, dual-neuromodulation responders could consist of responders of frontal tDCS and temporal TMS. In addition, abnormal activity in the frontal or temporal area of the responders is presumed to be modulated by treatment and will be suggested as the target areas in future studies.